Author Correction: Chemically intuited, large-scale screening of MOFs by machine learning techniques. (December 2017) - Borboudakis, Giorgos; Stergiannakos, Taxiarchis; Frysali, Maria; Klontzas, Emmanuel; Tsamardinos, Ioannis; Froudakis, George
A correction to this article has been published and is linked from the HTML version of this article.